2021
DOI: 10.1001/jamacardio.2020.6566
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic West African Ancestry, Blood Pressure Response to Therapy, and Cardiovascular Risk Among Self-reported Black Individuals in the Systolic Blood Pressure Reduction Intervention Trial (SPRINT)

Abstract: IMPORTANCE Self-identified Black race is associated with higher hypertension prevalence and worse blood pressure (BP) control compared with other race/ethnic groups. The contribution of genetic West African ancestry to these racial disparities appears not to have been completely determined.OBJECTIVE To determine the association between the proportion of West African ancestry with the response to antihypertensive medication, BP control, kidney function, and risk of adverse cardiovascular (CV) events among self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Descriptive studies of African admixture in the US report marked variability in percentage African ancestry by geographic regions, with the highest levels of African genetic ancestry observed in rural southern states [ 23 ]. In most studies, adjusting for socioeconomic and lifestyle variables attenuates the relationship between African ancestry to non-significance [ 36 , 46 , 63 , 66 ]. For example, Non et al reported no evidence of an association between West African ancestry and hypertension following adjustment for education in a study of SIAA [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive studies of African admixture in the US report marked variability in percentage African ancestry by geographic regions, with the highest levels of African genetic ancestry observed in rural southern states [ 23 ]. In most studies, adjusting for socioeconomic and lifestyle variables attenuates the relationship between African ancestry to non-significance [ 36 , 46 , 63 , 66 ]. For example, Non et al reported no evidence of an association between West African ancestry and hypertension following adjustment for education in a study of SIAA [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19]22 Genetic ancestry proportions have been previously noted to be associated with poor cardiometabolic phenotype and with adverse cardiovascular events. 23,24 Importantly, the relationship between the genetic ancestry proportion and incident diabetes among high-risk, hypertensive Black individuals has not been previously evaluated.…”
mentioning
confidence: 99%
“…It is not immediately clear, for any biological variable, the extent to which biology is "inherent" or the result of external influences. What is clear is that social determinants play a large role in health outcomes influenced by biology, including blood pressure regulation [17,18]. In the context of areas such as epigenetics, within-life modification of the genome by a range of environmental influences, it is unclear what the term "inherent" even really means.…”
mentioning
confidence: 99%